GREEN BUSINESS PRACTICES AND EMPLOYEE JOB SATISFACTION IN ORGANIZATIONS - OBIALOR, DONATUS CHUKWUEMEKA; UBONG, HARRISON, QUEEN; ETTE, BLESSING OTTOBONG; UWAKWE, UCHENNA EMMANUEL (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The aftermaths of the recession have inspired more businesses to incorporate sustainability into their business strategies. Sluggish growth, low productivity and other social environmental and organizational factors have had an effect on the workforce. The unprecedented effects and outcome of dissatisfaction and disengagement of employees worldwide have called managers of organizations to find various initiatives to improve employee satisfaction and engagement. The convenience sampling method was used to determine a sample size of 100 samples. The study adopted a descriptive statistic of mean and standard deviation, and used Spearman’s co-relational study to examine the effect of the relationship between Sustainable Practices and Employee job Satisfaction in Champion Breweries Plc Uyo. Result shows that Employee Satisfaction have a significant effect on Sustainable business Practices. The study recommends that firms should embrace policies that would efficiently lead to sustainability and satisfaction of employees. The study concludes that Green Practices promotes a vision for the accountability and satisfaction of businesses in a wide range of employees, stakeholders and investors.